(untitled) (Al-Academy, 2023)
The aim of the current study is to investigate the effect of “the effectiveness of the mental visualization strategy in developing the artistic expression of the fifth-grade students in the subject of art education”. Choosing it as a field to apply the experiment intentionally, because the researcher is an educational supervisor at the school and is suitable for the application of the current research, and she chose the experimental design, as the sample size reached (73) male and female students, and the total number of them after exclusion became (60) male and female students divided into two groups, one of them (experimental). ) by (30) male and female students, and the second (control) by (30) male and female students as well, and the researcher rewarded the two groups statistically in the variables, gender, number, age, educational attainment of parents, the researcher identified the topics for the art education subject that she will teach during the period of the experiment, Teaching plans were prepared and drafted, and the plans were presented to a group of experts for the purpose of judging their validity. The necessary modifications were made and the plans are ready for implementation in the light of their opinions. For the purpose of developing the artistic expression of the students of the two research groups in the material that the researcher taught, the researcher prepared a tool and its validity was confirmed. And its stability, after completing the collection of the drawings of the fifth grade primary students, and the researcher used: - The test equation (T-Test), the Cooper equation, and the researcher used the (Pearson) equation. - test) two independent samples to find out the significance of the difference between the two groups, and the t-test (t-test) for two related samples to know the significance of the difference between the pre and post-test for one group. The members of the two research groups and in favor of the students of the experimental group who were taught according to the mental imagery strategy. The current study, the researcher concluded that teaching with mental imagery strategy increases the effectiveness of the development of artistic expression among fifth grade students in art education, and recommended the inclusion of teachers in training courses in teaching methods and active learning strategies, and suggested conducting similar studies to develop Visual thinking expression and spatial ability among students.